Analysis of Charismatic Deposits and the Staging of the President of Madrid’s Speeches. A Case Study - Luis Ramos (Siyasal: Journal of Political Sciences)
This paper analyzes the modern charismatic phenomenon which takes place in a personalization of politics paradigm that places political parties far from the political perceptions of society, whereas leaders look much closer to citizens. The first part is structured as a theoretical discussion around charisma and the mass concept, considering Weber’s definition of charisma as domination. The reader will find research about how Weber’s concept resembles the actual one. In order to link this with the personalization of politics, we analyze the ancient and actual charismatic items hidden in speech. The contextual and methodological frameworks are comprised in the following part, which consists of a constructivist inductive speech and the staging analysis of Isabel Díaz Ayuso, President of the Community of Madrid from 2019, when she almost lost her first election, to nowadays, when she recently got an absolute majority at Madrid’s Assembly. The third part contains a discussion of the results obtained. The last part is the conclusion, which shows Díaz Ayuso as a semi-pure charismatic leader inserted in a personalization of politics paradigm that has used media and drama as tools to maintain power and who has tried to de-routinize charisma through her most mediatic speeches.